(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The global production of bananas exceeds 150 million tons annually, generating substantial waste in the form of banana peels, which constitute 35–40% of the fruit’s mass. These peels, rich in dietary fiber (up to 50%), polyphenols, pectin, and minerals, represent a valuable resource for food technologies. However, their utilization is hindered by the presence of antinutritional compounds, such as oxalates (0.1-0.5% dry weight) and cyanides (<1 mg/kg), which pose health risks and affect product safety. This article addresses the urgent need to develop effective methods for removing these compounds to enable the safe incorporation of banana peels into food products, contributing to waste reduction and sustainable food production. The primary objective of this study is to evaluate chemical, thermal, enzymatic, and combined methods for extracting oxalates and cyanides from banana peels, assess their impact on bioactive compounds, and demonstrate practical applications in food formulations. Experimental procedures involved processing 1 kg of fresh Cavendish banana peels using: (1) chemical extraction with 0.1 M acetic acid and 0.5% NaHCO₃, (2) thermal treatment via blanching (100°C, 8 min) and drying (65°C), (3) enzymatic treatment with oxalate oxidase and cyanide hydratase, and (4) a combined blanching-enzymatic approach. Analytical methods included HPLC for oxalates and spectrophotometry for cyanides. Results showed that the combined method was the most effective, removing 85% of oxalates and 97% of cyanides while preserving 92% of polyphenols. Chemical and enzymatic methods achieved 60–78% oxalate reduction, while thermal treatment was more effective for cyanides (87%). Processed peels were incorporated into bread (10% peel powder), yogurt (0.5% pectin), and energy bars (15% peel powder), increasing fiber content by 20–25% and antioxidant activity by 15%, with acceptable sensory scores (4.3–4.5/5). The study concludes that banana peels can be safely utilized in food technologies following proper processing, with combined methods offering optimal safety and functionality. These findings support sustainable food production by valorizing waste, though challenges remain in scaling technologies and ensuring regulatory compliance. Future research should focus on cost-effective processing and standardized protocols to facilitate industrial adoption.